Buying Intention on Electric Cars in Jabodetabek Using Combined TAM and TPB (C-TAM-TPB) - Muhammad Naufal; Hardiana Widyastuti; Indra Refipal Sembiring; Mokhamad Syaefudin Andrianto (School of Business, Bogor Agricultural University (SB-IPB), 2024)
The use of motorized vehicles in Indonesia increasing from year to year. This has impacted higher air pollution. The use of electric cars was considered to reduce air pollution. However, the use of electric cars in Indonesia still experienced obstacles. This study aimed to analyze the factors that influenced people to buy electric cars in Jabodetabek through the integration/combination of TAM (Technology Acceptance Model) and TPB (Theory of Planned Behavior) or C-TAM-TPB, which were expanded by adding variables of Price Value, Perceived Risk, Environmental Awareness, and Infrastructure Barrier. There are 200 respondents participated in the study. They are selected using non-probability sampling with purposive sampling method. The data analysis technique used descriptive analysis and SEM PLS. The results of this study indicated that perceived usefulness and perceived ease of use had a positive influence on attitude. The variables attitude, perceived behavioural control, and price value had a positive influence on the intention to buy electric cars, while subjective norm, perceived risk, environmental awareness, and infrastructure barriers had no significant effect on the intention to buy electric cars. Keywords: buying intention, C-TAM-TPB, electric car, infrastructure barriers